Optimasi Jumlah Kedatangan Bus Transjakarta Koridor 1 untuk Melayani Penumpang pada Jam Sibuk Menggunakan Simulasi - Mirna Lusiani; William William (Universitas Bunda Mulia, 2020)
Public transportation plays an important role in meeting people's needs for traveling. In a big city like DKI Jakarta, public transportation plays an important role in supporting the daily activities of its people. Transjakarta is one of the mass public transportation (bus rapid transit) provided by the local government for the community. One of the corridors that have the highest number of passengers is corridor 1 which serves the Blok M - Kota route. The problem that occurs is the irregularity in the scheduling system and the operation of the buses which are considered to be less than optimal, as a result, many buses are idle or buses travel but only carry a few passengers, especially during peak hours on weekdays. To solve this problem, it is necessary to conduct research that regulates the scheduling of bus arrivals at peak hours to serve a large number of passengers. The method used in this research is a simulation by determining the headway timing and determining the number of buses to operate as optimally as possible. The proposed simulation is made of 3 new scenarios and 1 proposed scenario for real-time conditions. Based on the simulation results, the determination of the headway time of 9 minutes between arrivals and 13 buses used during rush hour, from the previous one with a headway time of 4 minutes between arrivals, but the buses used are 30 buses during peak hours. This proposal given is to save bus usage and maximize the utility of the bus.